SIMULASI PENJUALAN SPARE PART LAPTOP MENGGUNAKAN METODE MONTE CARLO (STUDI KASUS: TOKO JAMBEE COMPUTER) - Efitra Efitra (Jaringan Sistem Informasi Robotik-JSR, 2020)
Abstract Laptop Spare parts are Laptop tools that are the primary needs of every Laptop user such as Batery, Keyboard, Led and Adapter. Spare part will be sold based on the frequency of market demand. To estimate the market demand of how good the Spare part supplies are, it is necessary to implement Monte carlo simulation strategy. Monte carlo simulation is a technique to predict the estimated average demand and sales revenue for the upcoming year 2018 based on 2017's previous year data. The spere part sales simulation technique specifies the Spare part supply Probability Distribution with the frequency of demand resulting in Cumulative Distribution of each variable. Next determine the Interval of the Random Number (Random Numbers) and select the Random Number so as to Generate the Simulation of the experimental circuit. The result of the experiment of this method is to get the average amount of sales demand and the average amount of revenue. Estimates of the Monte carlo simulation strategic plan that has been done will produce an estimated information on the average number of sales as 143 units and the estimated average amount of revenue of Rp. Rp.48.140.000, -. With the number of calculations obtained then the laptop spare parts to be sold can be estimated and inventory can be provided to meet market demand in 2018. Keywords : Simulation, Sales, Spare Spart, Algorithm, Monte carlo